Pengaruh Capital Adequacy Ratio (CAR), Dan Beban Operasional Pendapatan Operasional (BOPO), Terhadap Return On Asset (ROA). (Studi Kasus Pada PT. Bank Central Asia,Tbk. Periode 2014-2023) - Robby Alwan Fauzi; Lisdawati Lisdawati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study analyzes the effect of Capital Adequacy Ratio (CAR) and Operating Expenses on Operating Income (BOPO) on Return on Asset (ROA) at PT Bank Central Asia Tbk. for the period 2014-2023. The research population is PT Bank Central Asia Tbk. which is listed on the Indonesia Stock Exchange. The sample was taken by purposive sampling method from the financial statements published during the period. The data used is secondary quantitative data. The analysis was carried out using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS version 26. The results show that CAR has no significant effect on ROA (t count -1.694 < t table 1.8945, p = 0.129), while BOPO has a significant negative effect (t count -4.437 < t table 1.8945, p = 0.002). The F test shows that CAR and BOPO simultaneously affect ROA (f count 9.134 > f table 4.737, p = 0.011), with an R Square of 87.3%, which means that changes in ROA are influenced by these two variables